Жизнь и творчество А.С. Пушкина - Кулешов Василий Иванович (Худож. лит., 1987)
Экземпляры: (20190416) / Инвентарный номер: 20650 / Цена: 1.50 / Сис.шифр: 83.3(2=Рус)5-8 Пушкин / Авт.знак: К90 / ГРНТИ: 17.09 / ББК: 83.3(2=Рус)5-8 Пушкин 4